Vacancy durations and entry wages: Evidence from linked vacancy-employer-employee data - Andreas Kettemann; Andreas I. Mueller; Josef Zweimüller (University of Zurich, Department of Economics, 2018)
This paper explores the relationship between the duration of a vacancy and the starting wage of a new job, using unusually informative data comprising detailed information on vacancies, the establishments posting the vacancies, and the workers eventually filling the vacancies. We find that vacancy durations are negatively correlated with the starting wage and that this negative association is particularly strong with the establishment component of the starting wage. We also confirm previous findings that growing establishments fill their vacancies faster. To understand the relationship between establishment growth, vacancy filling and entry wages, we calibrate a model with directed search and ex-ante heterogeneous workers and firms. We find a strong tension between matching the sharp increase in vacancy filling for growing firms and the response of vacancy filling to firm-level wages. We discuss the implications of this finding as well as potential resolutions.
Keywords: E24; J31; J63; 330; vacancy posting; vacancy duration; recruiting; search; wages